Gerontological contributions to the care of elderly people in long-term care facilities - Vanessa da Silva Antonio Coimbra; Rose Mary Costa Rosa Andrade Silva; Fabiana Lopes Joaquim; Eliane Ramos Pereira
ABSTRACT Objective: To analyze Brazilian scientific productions from the last 11 years which show the contributions of nursing to elderly people in long-term care facilities. Method: This is an integrative literature review. The search took place in the Virtual Health Library (VHL) in the BDENF and LILACS databases and the SCIELO virtual library, between June and October 2016, using the keyword long-term care facility and the descriptors nursing and geriatrics. Results: Eleven studies were selected, published 2005 and 2016, with various methodological approaches that enabled discussion of the proposed objective. Conclusion: The contributions of nursing to institutionalized elderly people were linked to health promotion measures, as well as simple interventions, such as listening, interacting, offering recreation and helping in psychoaffective relationships. These activities contributed to raising the self-esteem of the individuals.